The effect of Directed medical play on the severity of pain during burn dressing change: Clinical Randomized trial - Atefeh Mosavi; Shadi Asgari; Yousef Rahimi; Naser Mohammad gholi mezerji (مراقبت پرستاری و مامایی ابن سینا, 2019)
Introduction: Pain management in children with burn is one of the most important issues in pediatric medicine. Non-pharmacological methods of pain control can play an important role in patients. Therefore this study was conducted to investigate the effect of medical directed play on the severity of pain during burn dressing change. Methods: To conduct this two-group clinical trial, 78 children of 3-6 years old with burn surface area ranging less than 25% who had referred to Shahid Motahari Medical Center for their first burn dressing change, were selected. After obtaining the ethics approval for conducting the study, the patients were placed as random allocation in control and intervention groups. For the intervention group, the pre-dressed directed medical play was done and routine care was taken for the control group. The FLACC scale was used in both groups to measure the severity of pain before and during the dressing; the arterial blood oxygen level and heart rate were also measured and compared. For data analysis, SPSS 20 was used. Results: There were significant differences between the two groups during burn dressing change of mean pain (P=0.041) and pulse (P=0.037), and the mean of both indices in the control group was high. The mean of the arterial blood oxygen level during burn dressing change did not differ significantly between the two groups (P=1). Conclusion: Directed Medical play effectively reduces the pain of pediatric burn dressing change. This technique is cost-effective, so it can be widely used for pain management in pediatric department.